Influence of steroids and methotrexate on wound complications after elective rheumatoid hand and wrist surgery. - Jain, A; Witbreuk, M; Ball, C; Nanchahal, J (2002)
Eighty patients with rheumatoid arthritis who had 129 surgical procedures on the hand and wrist over a 5-year period were reviewed. All patients continued with their usual medication throughout the perioperative period. There were 2 pin track infections and 1 wound infection in patients taking methotrexate alone (3 of 48), 1 wound dehiscence in a patient taking steroids without methotrexate (1 of 30), 1 wound infection in a patient taking both drugs (1 of 30), and 2 wound infections in patients taking neither of these drugs (2 of 21). There was no statistically significant risk of wound infection or breakdown in patients taking methotrexate or steroids or both. Rheumatoid patients with diabetes had an increased risk of wound infection (33%) compared with patients without (3.3%). No disease flare-ups occurred within 3 months of surgery. We recommend that these drugs be continued throughout the surgical and postoperative rehabilitation period.